An Investigation of WO3/V2O5/TiO2 Catalysts: Effects of WO3 on Morphology, Thermal Stability, and Activity for the Catalytic Oxidation of Dimethyl Sulfide - Gaytri Sharma; Endalkachew Sahle-Demessie; Catherine B. Almquist (Molecules)
WO3/V2O5/TiO2 (WxV5TiO2) catalysts were prepared via a wet incipient method with a V/Ti mass ratio = 0.05 and a W/Ti mass ratio varying from 0 to 0.10. The catalysts were calcined in air for 24 h at temperatures of 400 °C, 500 °C, 550 °C, and 600 °C. The presence of WO3 on WxV5TiO2 catalysts inhibits morphological and crystal structure transformations as the calcination temperature increases from 400 °C to 600 °C. The results of this study give evidence that the active component of the catalyst is V on anatase TiO2. Therefore, the incorporation of WO3 onto an anatase TiO2 support widens the temperature range at which the WO3/V2O5/TiO2 catalyst maintains the anatase crystal structure and, hence, the performance of the catalyst. The catalytic oxidation of dimethyl sulfide (DMS) was used as a probe reaction to evaluate catalytic activity. The results indicate that WO3/V2O5/TiO2 catalysts are capable of effectively oxidizing DMS at relatively low reaction temperatures (250 °C), even under conditions of an elevated DMS concentration in air (1.6 vol%).